2017
DOI: 10.1371/journal.pone.0182138
|View full text |Cite
|
Sign up to set email alerts
|

Exploring public genomics data for population pharmacogenomics

Abstract: Racial and ethnic differences in drug responses are now well studied and documented. Pharmacogenomics research seeks to unravel the genetic underpinnings of inter-individual variability with the aim of tailored-made theranostics and therapeutics. Taking into account the differential expression of pharmacogenes coding for key metabolic enzymes and transporters that affect drug pharmacokinetics and pharmacodynamics, we advise that data interpretation and analysis need to occur in light of geographical ancestry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…This locus exhibits significant difference between Africans and non-Africans [ 35 ] which is evident in our gPC plot as well. Lakiotaki et al [ 36 ] identified this variant to belong to the 10 most different ones in worldwide populations. Unlike the previously mentioned locus in VKORC1, the frequency of globally minor allele of rs2242480 in the investigated Roma population (0.3012) is higher than in European populations and corresponds to the frequency range of South Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…This locus exhibits significant difference between Africans and non-Africans [ 35 ] which is evident in our gPC plot as well. Lakiotaki et al [ 36 ] identified this variant to belong to the 10 most different ones in worldwide populations. Unlike the previously mentioned locus in VKORC1, the frequency of globally minor allele of rs2242480 in the investigated Roma population (0.3012) is higher than in European populations and corresponds to the frequency range of South Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, with decreasing costs of sequencing allowing for studies with larger numbers of participants common variants in non-Caucasian populations and rare variants in all populations are now being identified. [23][24][25][26] Even with robust research findings, clinical translation of basic research findings remains a challenge. For example, despite the growing body of research characterizing PGx variants with clinical value (Table 2) and leading to curation of over 650 medications in PharmGKB, there are currently only approximately 132 medications that have annotated clinical guidelines.…”
Section: Clinical Researchmentioning
confidence: 99%
“…We posit that GA provides a number of advantages over racial/ethnic categories for biomedical research: (i) it can be characterized independently of the social and environmental dimensions of race/ethnicity, (ii) it can be measured objectively and with precision, and (iii) it can be quantified as a continuous variable, as opposed to categorical racial/ethnic labels. Indeed, a number of recent studies have focused on PGx variation among populations defined by GA rather than racial and ethnic groups [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%